2017
DOI: 10.7150/thno.16638
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 68Ga-HBED-CC PSMA-PET/CT and multiparametric MRI for gross tumour volume detection in patients with primary prostate cancer based on slice by slice comparison with histopathology

Abstract: Purpose: The exact detection and delineation of the intraprostatic tumour burden is crucial for treatment planning in primary prostate cancer (PCa). We compared 68 Ga-HBED-CC-PSMA PET/CT with multiparametric MRI (mpMRI) for diagnosis and tumour delineation in patients with primary PCa based on slice by slice correlation with histopathological reference material. Methodology: Seven patients with histopathologically proven primary PCa underwent 68 Ga-HBED-CC-PSMA PET/CT and MRI followed by radical prostatectomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(138 citation statements)
references
References 31 publications
(52 reference statements)
5
127
1
3
Order By: Relevance
“…Here, 68 Ga‐PSMA PET/MRI significantly outperformed multiparametric MRI or 68 Ga‐PSMA PET with a sensitivity and specificity for tumor localization on a sextant base of 76% and 97% (58% and 82% for multiparametric MRI, 64% and 94% for 68 Ga‐PSMA PET, respectively) . Furthermore, several studies assessing intraprostatic tumor localization in correlation to histopathology by 68 Ga‐PSMA PET/CT showed significantly higher 68 Ga‐PSMA uptake in positive segments compared with negative segments (SUV max 11.8 vs 4.9 and 11.0 vs 2.7, respectively, P < 0.001 each) …”
Section: Prostate Cancermentioning
confidence: 81%
“…Here, 68 Ga‐PSMA PET/MRI significantly outperformed multiparametric MRI or 68 Ga‐PSMA PET with a sensitivity and specificity for tumor localization on a sextant base of 76% and 97% (58% and 82% for multiparametric MRI, 64% and 94% for 68 Ga‐PSMA PET, respectively) . Furthermore, several studies assessing intraprostatic tumor localization in correlation to histopathology by 68 Ga‐PSMA PET/CT showed significantly higher 68 Ga‐PSMA uptake in positive segments compared with negative segments (SUV max 11.8 vs 4.9 and 11.0 vs 2.7, respectively, P < 0.001 each) …”
Section: Prostate Cancermentioning
confidence: 81%
“…Increasing numbers of studies have investigated the potential of 68 Ga-PSMA-11 for intraprostatic tumor localization (97)(98)(99)(100)(101)(102). For example, on the basis of a 6-segment model per slice, histopathologically positive segments (n 5 100 in 21 patients) had significantly higher 68 Ga-PSMA-11 uptake than negative segments (SUV max , 11.8 vs. 4.9), suggesting an SUV max of 6.5 as an optimal discriminator (sensitivity of 67% and specificity of 92% for the detection of tumor-involved segments) (97).…”
Section: Primary Stagingmentioning
confidence: 99%
“…With regard to intraprostatic tumor localization by 68 Ga-PSMA-11 PET/CT, imaging findings were correlated with histopathology using segment-or voxel-based approaches in several studies (50)(51)(52). These studies demonstrated relatively similar results, with a significantly higher 68 Ga-PSMA-11 uptake in positive segments than in negative segments (SUV max of 11.8 vs. 4.9 and 11.0 vs. 2.7, respectively, P , 0.001 each) (50,51).…”
Section: Primary Stagingmentioning
confidence: 99%